2007
DOI: 10.1097/sle.0b013e318030b0f2
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Bioabsorbable Seamguard During Laparoscopic Appendectomy

Abstract: The laparoscopic approach to appendectomy for acute appendicitis is becoming increasingly favored among surgeons. Endoscopic stapling remains a common approach for division of the appendix and mesoappendix, but staple line bleeding along the mesentery is commonly observed, occasionally demanding surgical control for complete hemostasis. Bioabsorbable seamguard was used as an adjunct to endoscopic stapling of the mesoappendix in 33 consecutive adult patients during laparoscopic appendectomy for acute appendicit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…This material is degraded through a combination of hydrolytic and enzymatic pathways; it is biocompatible and nonantigenic. Seamguard Ò has been used to assist surgeons performing appendectomies, mesenteric vascular resections, pancreatectomies, and a variety of colorectal procedures [31][32][33][34][35]. Prospective, randomized, clinical trials have shown that Seamguard Ò minimizes staple-line bleeding and leakage and reduces operating time [15,36].…”
Section: Discussionmentioning
confidence: 99%
“…This material is degraded through a combination of hydrolytic and enzymatic pathways; it is biocompatible and nonantigenic. Seamguard Ò has been used to assist surgeons performing appendectomies, mesenteric vascular resections, pancreatectomies, and a variety of colorectal procedures [31][32][33][34][35]. Prospective, randomized, clinical trials have shown that Seamguard Ò minimizes staple-line bleeding and leakage and reduces operating time [15,36].…”
Section: Discussionmentioning
confidence: 99%
“…SeamGuard has been used to assist surgeons performing appendectomies, mesenteric vascular resections, pancreatectomies, and a variety of colorectal procedures [5,8,[46][47][48]. Prospective randomized clinical trials have shown SeamGuard minimizes staple-line bleeding and leakage and reduces operating time [24,49].…”
Section: Buttress Materialsmentioning
confidence: 99%
“…12,13 Studies have shown reduced rates of bleeding and anastomosis leakage with its use in colon surgeries 14 and in appendectomies. 15 Lower rates of intraoperative bleeding, shorter surgical times, and reduced abscess formation with its use in bariatric surgery 16 have been reported.…”
Section: Discussionmentioning
confidence: 97%